Simple and rapid hplc-uv methods for gabapentin quantification in human plasma and urine: Applicability in pharmacokinetics and drug monitoring - Yamamoto, Priscila Akemi [UNESP]; Benzi, Jhohann Richard de Lima; de Moraes, Natália Valadares [UNESP] (Editora Cubo, 2021)
Aim: We aimed to develop methods to determine gabapentin (GAB) in biological samples using high-performance liquid chromatography (HPLC) with application in pharmacokinetics and therapeutic drug monitoring. Methods: Simple, rapid and efficient HPLC-UV methods to quantify GAB in human plasma and urine were developed and validated for clinical analysis of GAB. The 1-fluoro-2,4-dinitrobenzene (FDNB) was used as derivatization agent. For plasma samples, protein precipitation using acetonitrile was performed, before the derivatization reaction. Urine samples were cleaned-up by liquid-liquid extraction with dichloromethane:n-butanol (1:1, v/v) after derivatized. Amlodipine besilate was used as internal standard (IS). Results: Gabapentin and IS were resolved on LiChrospher® C18 RP column and a mixture of 50 mM sodium phosphate buffer (pH 3.9):methanol (27:73, v/v) as mobile phase, at 1.2 mL/min. The methods used small sample volumes, 100 and 50 µL of plasma and urine, respectively. Linearity was obtained in the interval of 0.2-14 µg/mL in plasma and 2-120 µg/mL in urine. Both methods showed to be selective, without carry-over effect, precise, accurate and stable in different conditions. GAB plasma concentration in patients receiving 600 to 3600 mg/day of GAB ranged between 0.40 to 11.94 µg/mL at steady-state. Conclusions: The methods described in this study were simple, rapid and fulfill all validation requirements. They were easily and successfully applied for population pharmacokinetics and therapeutic drug monitoring of GAB in patients with chronic pain.
Keywords: Gabapentin; HPLC; Plasma; Urine